Adaptation of a real-time RT-PCR assay for the detection of Schmallenberg virus - Rios, Liliam; Frías, María T.; Pérez, Lester J. (Revista de Salud Animal, 2014)
Schmallenberg virus was first detected in Germany in October 2011, associated with congenital malformations in cattle, sheep and goats. This novel emergent agent causes mild disease in cattle with decreased milk production, fever and diarrhea. In March 2012, the German Institute of Diagnostic Virology, Friedrich-Loeffler-Institut, reported the development and validation of a real-time RT-PCR for the diagnosis of this new virus. The Animal Virology Laboratory at the National Center for Animal and Plant Health in Cuba has adapted the protocol previously reported on the LightCycler platforms using two different mix conditions. In all cases, amplification curves obtained were specific and all the dilutions tested showed an increase in the Ct-values. Nevertheless, the sensitivity of the test was not affected. Thus, the test for Schmallenberg virus detection is enabled for the possible emergency of this agent in Cuba.